THE BENEFICIAL EFFECT OF Moringa Oleifera LEAVES ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA: A SYSTEMATIC REVIEW - Badri, Baarizah Febriana; Indarto, Dono; Ardyanto, Tonang Dwi; Avelia, Annisa (Universitas Aisyah Pringsewu, 2024)
Anemia is a serious maternal health problem that can result in long-term negative impacts such as preeclampsia, hemorrhage before and after delivery, stunting, reduced baby immunity, fetal retardation growth, and fetal death. Moringa oleifera is a miracle plant that has been used for anemia treatment. This study aimed to analyze systematically the effect of M. oleifera leaves on hemoglobin levels and dietary intake of iron and zinc in pregnant women with anemia. Our study used the Cochrane tool to select all randomized control trial (RCT) articles and met the requirements of the PRISMA diagram, filtered using some keywords: pregnant women, anemia, M.oleifera powder, and Fe supplements. The selected articles were further screened using the Population, Intervention, Comparator, Outcomes, and Study Type (PICOS) protocol and assessed for their quality using the Cochrane tool bias risks. Five full-text articles used M.oleifera leaves for anemia treatment in women with their first and or third trimester pregnancies. However, increased Hb levels in pregnant women who consumed 100g of fresh M.oleifera leaves with iron supplementation were higher than that of pregnant women who consumed M oleifera powder and extract. In addition, only one full-text article reported dietary intake of Fe and Zn as secondary outcomes after treating M. oleifera leaves. In conclusion, the administration of M. oleifera leaves has a minor effect on Hb levels and no effect on dietary intake of Fe and Zn in pregnant women with anemia.